At the threshold : contemporary theatre, art, and music of Iran - Esfandiary, Rana (London ; New York : Routledge, 2023)
"This book examines the performance strategies used by contemporary Iranian artists and activists to reimagine "Iranian-ness" in the context of Iran's local, regional, and global position. This study identifies the important social and political interventions made by theatrical and performance pieces, visual art, and electronic music that articulate and reformulate Iranian-ness by breaking away from fixed and constructed stereotypes projected on them by both the Islamic regime and Western power. This book explores the reception and context within which artworks become meaningful performative acts. Looking closely at the works of a notable female Iranian photographer, Shadi Ghadirian, in conjunction with the new generation of Iranian nonconformist artists/activists such as Tahmineh Monzavi and Hedieh Ahmadi; the visionary theatre productions of Ali Akbar Alizad; and radically untraditional sound/noise of the electronic music movement in Tehran, this book calls attention to the Iran-based artists who are tirelessly trying to raise awareness regarding the political violence imposed on Iranian identity at the legal (top-down) and everyday (bottom-up) levels. This volume will be of great interest to student and scholars in theatre and performance, photography, art, music, sociology, and politics"--
Preface and Acknowledgments; Introduction: The Borders of Persia(n); Chapter 1: Monologues of Resistance; Chapter 2: Bewildered They Stood, Like an Empty Oath, Like a Solemn Kurd: Ali Akbar Alizad and his Plea for Justice; Chapter 3: Off of the White Light and into a Spiral Pattern; Chapter 4: Em-Bracing the Liminal rather than Nostalgia; Conclusion: Circling in a Cul-de-sac
Keywords: Arts, Iranian -- 21st century -- Themes, motives; National characteristics, Iranian, in art; PERFORMING ARTS / Theater / General; PERFORMING ARTS / General